Kemunduran Mutu Fisik Dendeng Cumi-Cumi (Loligo Sp) Dengan Berbagai Jenis Kemasan (Standing Pouch, Cup Dan Plastik) - Leni Lasmi; Tri Wahyuni (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2023)
Dendeng is a semi-wet form of food which is usually made of meat or fish, thin and wide, seasoned and dried. The processing is by soaking the raw materials into the spices for about one day and then putting it in the oven. This study aims is to describe duration of the squid jerky in some packages thourgh the scoring test of squid jerky with various types of packaging, namely Standing Pouch, Cup and Plastic. The results of the scoring test show that the deterioration of quality by means of the scoring test can be seen on the 55th day with a value of 3.11 in the Cup packaging, 2.96 Standing Pouch packaging and 3.52 Plastic packaging and until the 70 the day with a value of 1.76 in the Cup packaging. 1.67 Standing Pouch packages and 1.41 Plasik packages.